Apache Flume: distributed log collection for Hadoop : design and implement a series of Flume agents to send streamed data into Hadoop - Hoffman, Steve (Community experience distilled., 2015)
If you are a Hadoop programmer who wants to learn about Flume to be able to move datasets into Hadoop in a timely and replicable manner, then this book is ideal for you. No prior knowledge about Apache Flume is necessary, but a basic knowledge of Hadoop and the Hadoop File System (HDFS) is assumed.